1989
DOI: 10.1055/s-2008-1046969
|View full text |Cite
|
Sign up to set email alerts
|

Die Synovialhöhle des Kniegelenkes und ihre großen kommunizierenden Bursen

Abstract: The knee joint, its physiological details and normal variants have been studied in about 2,000 arthrograms. The functional anatomy and the biomechanics of the joint are described and the pathogenetic significance of the septum and of the suprapatellar bursa and of the popliteal capsular enlargement are discussed. The width of the opening in the septum, the involvement of the septum in synovial processes, absence of communication between the bursa and the newly described ventral 'synovial cysts' are potential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…By means of inflation it was possible to also d e m o n s t r a t e those details which were disguised or could not be demonstrated at all [7] when positive contrast media were used. The anatomical specimens permitted a direct e x a m i n a t i o n o f the variable structures and spaces of the knee-joint cavity.…”
Section: Fig3mentioning
confidence: 98%
“…By means of inflation it was possible to also d e m o n s t r a t e those details which were disguised or could not be demonstrated at all [7] when positive contrast media were used. The anatomical specimens permitted a direct e x a m i n a t i o n o f the variable structures and spaces of the knee-joint cavity.…”
Section: Fig3mentioning
confidence: 98%
“…In literature review, the reported incidence of each plicae is controversial. 2,3,6,10,11,[13][14][15][16] In our study including 400 knees in 363 patients, 12 incidence of the synovial plica at the knees were: suprapatellar plica, 87.0%; mediopatellar plica, 72.0%; infrapatellar plica, 86.0%; and lateral patellar plica, 1.3%. These plicae were at first considered abnormal when seen at arthroscopy and then excised.…”
Section: Introductionmentioning
confidence: 97%